RELATIONSHIP BETWEEN CDCYNERGY'S SOCIAL MARKETING MODEL WITH INTENTION OF HIV COUNSELING AND TESTING FOR PREGNANT WOMEN IN SURAKARTA INDONESIA - Endang Sutisna Sulaeman; Widana Primaningtyas; Heni Hastuti; Anak Agung Alit Kirti Estuti Narendra Putri; Reni Wijayanti; Yeremia Rante Ada; Abdul Rahman (Biomedika, 2021)
ABSTRACTHIV-AIDS epidemic is still becoming a global public health problem. More than 90% of HIV cases in children caused by transmission from their mother. Recent global efforts have focused on eliminating  HIV infection in children through HIV counseling and testing for pregnant women (pregnant women VCT). The CDCynergy's social marketing model is widely used as a guide to conceiving robust social marketing plans. This study aimed to analyze the relationship between 6 dimensions of CDCynergy's social marketing model with the VCT intention of pregnant women. An observational analytic method with a survey approach is chosen for this research and the sample size was 90 pregnant women. Closed questionnaire was used as a research instrument. The results of logistic regression analysis showed that the strength of the relationship between VCT intention of pregnant women with the variable "conduct market research" was 12,527 units (p= 0.002), respectively. Conduct market research was having the most dominant relationship with the dependent variable compared to the other variables. Market research plays a great role as the base for social marketing program. Hence, it needs stakeholders support to optimize market research, especially in order to increase the engagement of pregnant women to attend VCT.   Keywords: HIV, CDCynergy’s Social Marketing Model, Pregnant Women VCT. ABSTRAKEpidemi HIV-AIDS masih menjadi masalah kesehatan masyarakat global. Lebih dari 90% kasus HIV pada anak-anak karena penularan dari ibu ke anak. Akhir - akhir ini seluruh dunia telah berfokus untuk mengurangi infeksi HIV pada anak-anak melalui konseling dan skrinning HIV untuk wanita hamil (VCT ibu hamil). Model pemasaran sosial CDCynergy secara luas digunakan sebagai panduan untuk skrinning ibu hamil dengan perencanaan pemasaran sosial yang kuat. Penelitian ini bertujuan untuk menganalisis hubungan antara 6 dimensi model pemasaran sosial CDCynergy pada VCT ibu hamil. Metode penelitian dengan analitik observasional melalui pendekatan survei dengan jumlah sampel 90 orang ibu hamil. Kuesioner tertutup digunakan sebagai instrumen penelitian. Hasil analisis regresi logistik menunjukkan bahwa kekuatan hubungan antara VCT niat ibu hamil dengan variabel "melakukan riset pasar" masing-masing sebesar 12.527 unit (p= 0,002). Melakukan riset pasar memiliki hubungan yang paling dominan dengan variabel dependen dibandingkan dengan variabel lainnya. Riset pasar memainkan peran besar sebagai basis program pemasaran sosial. Oleh karena itu, perlu dukungan pemangku kepentingan untuk mengoptimalkan riset pasar, terutama dalam rangka meningkatkan keterlibatan ibu hamil untuk menghadiri VCT.   Kata kunci: HIV, Model Pemasaran Sosial CDCynergy, VCT Ibu Hamil